Does Moral Intensity Affect the Whistleblowing Intentions? - Waseem Yousaf; Raheel Jamil (iRASD Journal of Management)
The present study investigates the nexus between whistle-blowing triangle having components like Pressure/Financial Incentives, Opportunity, rationalization, and whistle-blowing intentions by focusing the moral intensity playing a moderating role in the Pakistani context to enhance the body of information on this subject by giving observational demonstrate. The sample in this research is taken from the Karachi Stock Exchange of Pakistan registered audit firms. PLS-PM method based analysis results found a significant relationship between whistle-blowing triangle components, whistle-blowing intentions, and moral intensity. We found that the most significant predictor of the auditor’s intentions to report the wrongdoing in Pakistan is an opportunity. Pressure/Financial Incentives and rationalization, the other components of the whistle-blowing triangle, also play a vital role in assisting the auditor’s whistle-blowing intentions. These investigation findings proposed that an opportunity is the priority factor for enhancing the auditor’s whistle-blowing intentions in Pakistan. Our results also concluded that the moral intensity significantly and positively moderates this relation among the whistle-blowing triangle and intentions to report the wrongdoing. This study also provides insights to the society in better understanding the whistle-blowing concept, an issue neglected by society.